1 / 4

50 likes | 230 Vues

5.6 Sum of Geometric Series (1/4). a(r n -1) r-1. a(1-r n ) 1-r. S n = for |r|>1. S n = for |r|<1. Term Number. First Term. Common Ratio. Sum (add) to n terms. 5.6 Sum of Geometric Series (2/4). Example: Find the sum of the first 10 terms of 2 + 6 + 18 + ….

Télécharger la présentation
## 5.6 Sum of Geometric Series (1/4)

**An Image/Link below is provided (as is) to download presentation**
Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.
Content is provided to you AS IS for your information and personal use only.
Download presentation by click this link.
While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.
During download, if you can't get a presentation, the file might be deleted by the publisher.

E N D

**5.6 Sum of Geometric Series (1/4)**a(rn-1) r-1 a(1-rn) 1-r Sn= for |r|>1 Sn= for |r|<1 Term Number First Term Common Ratio Sum (add) to n terms**5.6 Sum of Geometric Series (2/4)**Example: Find the sum of the first 10 terms of 2+6+18+ … a(rn – 1) r - 1 r = 6÷2 = 3 Sn = since |3|>1 a = 2 2x(310 – 1) 3 - 1 S10 = n = 10 = 59048**5.6 Sum of Geometric Series (3/4)**Example: Evaluate 2+6+18+ … + 486 Find n Find Sn a(rn – 1) r - 1 r = 6÷2 = 3 Tn = a rn – 1 Sn = since |3|>1 a = 2 486 = 2x3n – 1 2x(36 – 1) 3 - 1 Tn = 486 S6 = 3n – 1 = 243 log33n – 1 = log3243 = 728 n - 1 = log3243 ln 243 ln 3 n - 1 = n – 1 = 5 n = 6**5.6 Sum of Geometric Series (4/4)**Example: Evaluate a(rn – 1) r - 1 Sn = since |3|>1 9x(36 – 1) 3 - 1 S6 = a = 9 r = 3 n = 6 = 9837

More Related